A prostaglandin E2 receptor antagonist prevents pregnancies during a preclinical contraceptive trial with female macaques - Peluffo, Marina Cinthia (2014)
STUDY QUESTION Can administration of a prostaglandin (PG) E2 receptor 2 (PTGER2) antagonist prevent pregnancy in adult female monkeys by blocking periovulatory events in the follicle without altering menstrual cyclicity or general health? SUMMARY ANSWER This is the first study to demonstrate that a PTGER2 antagonist can serve as an effective non-hormonal contraceptive in primates. WHAT IS KNOWN ALREADY The requirement for PGE2 in ovulation and the release of an oocyte surrounded by expanded cumulus cells (cumulus–oocyte expansion; C-OE) was established through the generation of PTGS2 and PTGER2 null-mutant mice. A critical role for PGE2 in primate ovulation is supported by evidence that intrafollicular injection of indomethacin in rhesus monkeys suppressed follicle rupture, whereas co-injection of PGE2 with indomethacin resulted in ovulation. STUDY DESIGN, SIZE, DURATION First, controlled ovulation protocols were performed in adult, female rhesus monkeys to analyze the mRNA levels for genes encoding PGE2 synthesis and signaling components in the naturally selected pre-ovulatory follicle at different times after the ovulatory hCG stimulus (0, 12, 24, 36 h pre-ovulation; 36 h post-ovulation, n = 3–4/time point). Second, controlled ovarian stimulation cycles were utilized to obtain multiple cumulus–oocyte complexes (COCs) from rhesus monkeys to evaluate the role of PGE2 in C-OE in vitro (n = 3–4 animals/treatment; ≥3 COCs/animal/treatment). Third, adult cycling female cynomolgus macaques were randomly assigned (n = 10/group) to vehicle (control) or PTGER2 antagonist (BAY06) groups to perform a contraceptive trial. After the first treatment cycle, a male of proven fertility was introduced into each group and they remained housed together for the duration of the 5-month contraceptive trial that was followed by a post-treatment reversibility trial. PARTICIPANTS/MATERIALS, SETTING, METHODS Quantitative real-time PCR, COC culture and expansion, immunofluorescence/confocal microscopy, enzyme immunoassay, contraceptive trial, ultrasonography, complete blood counts, serum biochemistry tests and blood lipid profiles. MAIN RESULTS AND THE ROLE OF CHANCE Several mRNAs encoding proteins involved in PGE2 synthesis, metabolism and signaling increase (P < 0.05) in the periovulatory follicle after administration of an ovulatory hCG bolus. PGE2 signaling through PTGER2 induces cumulus cell expansion and production of hyaluronic acid, which are critical events for fertilization. Moreover, chronic administration of a selective PTGER2 antagonist resulted in a significant (P < 0.05 versus vehicle-treated controls) contraceptive effect without altering steroid hormone patterns or menstrual cyclicity during a 5-months contraceptive trial. Fertility recovered as early as 1 month after ending treatment. LIMITATIONS, REASONS FOR CAUTION This is a proof-of-concept study in a non-human primate model. Further investigations are warranted to elucidate the mechanism(s) of PTGER2 antagonist action in the primate ovary. Although PTGER2 antagonist treatment did not produce any obvious undesirable effects, improvements in the mode of administration, as well as the efficacy of these compounds, are necessary to consider such a contraceptive for women. WIDER IMPLICATIONS OF THE FINDINGS Monitoring as well as improving the efficacy and safety of female contraceptives is an important public health activity. Even though hormonal contraceptives are effective for women, concerns remain regarding their side-effects and long-term use because of the widespread actions of such steroidal products in many tissues. Moreover, some women cannot take hormones for medical reasons. Thus, development of non-hormonal contraceptives for women is warranted. STUDY FUNDING/COMPETING INTEREST(S) Supported by Bayer HealthCare Pharmaceuticals, The Eunice Kennedy Shriver NICHD Contraceptive Development and Research Center (U54 HD055744), NIH Office of the Director (Oregon National Primate Research Center P51 OD011092), and a Lalor Foundation Postdoctoral Basic Research Fellowship (MCP). The use of the Leica confocal was supported by grant number S10RR024585. Some of the authors (N.B., A.R., K.-H.F., U.F., B.B. and B.L.) are employees of Bayer Healthcare Pharma.